Sanitary quality of seeds of "pau-cigarra" (Senna multijuga) - Schultz, Vanessa Sperandio (2003)
The aim of this research was to identify fungi associated with "pau-cigarra" seeds (Senna multijuga). Evaluation was carried out in nine lots composed of seeds collected from mother trees at Atlantic Rain Forest located in Antonina, Morretes and Guaraqueçaba municipalities, Paraná state, Brazil. Sanitary analysis was carried out by adopting blotter test and agar plate test. Morphological characteristics were used for fungi identification. It was observed higher fungi frequency contaminating seeds over filter paper (blotter test) compared with agar plate test. Helminthosporium sp., Alternaria sp., Ulocladium sp., Pestalotia sp., Penicillium sp., Trichoderma sp., Chaetomium sp. and Monilia sp. were the most important genus found associated with S. multijuga seeds.